Complete transitioning to the radial approach for primary percutaneous coronary intervention: a real-world single-center registry of 1808 consecutive patients with acute ST-elevation myocardial infarction - Kedev, Sasko; Kalpak, Oliver; Dharma, Surya; Antov, Slobodan; Kostov, Jorgo; Pejkov, Hristo; Spiroski, Igor (My University, 2014)
To compare the short- and long-term outcomes of transradial approach (TRA) versus transfemoral approach (TFA) for primary percutaneous coronary intervention (PPCI) during a complete institutional transition from TFA to TRA.